Pendampingan dan Pelatihan Menghafal Al-Qur’an untuk Mengembangkan Program Tahfiz di Pesantren Sultan Hasanuddin, Gowa - Hakim, Azizul; Sabaruddin Garancang,; Sitti Aisyah Chalik,; Erlangga Syarifuddin,; Muhammad Ahmad, (KHIDMAH: Jurnal Pengabdian kepada Masyarakat, 2023)
The majority of people in Indonesia are Muslims, with the Qur'an and al-Sunnah as their guidelines. Nowadays, the activity of memorizing the Qur'an and the memorizers of the Qur'an in Indonesia is growing rapidly. This service was carried out to provide assistance and training in memorizing the Qur'an to students who participated in the tahfiz program at Pesantren Sultan Hasanuddin so that the students were able to memorize the Qur'an. Pesantren Sultan Hasanuddin is actually not a Tahfidz al-Qur'an Islamic Boarding School, but the desire of the students and their parents so that this new tahfiz program emerged in the Sultan Hasanuddin Islamic Boarding School environment as a positive response from the pesantren for parents and students who want to memorize the Qur'an. This service is carried out with the method of mentoring and training to students who take part in the tahfiz program which has been stopped due to the absence of a coach who is responsible for the program. After the service was carried out, the students who participated in the tahfiz program had a very high interest in memorizing the Qur'an. This shows that the tahfiz program needs to be developed.